PENGARUH STRESOR FISIK TERHADAP DISTRIBUSI SERT DAN INDEKS APOPTOSIS NEURON HIPOKAMPUS, SERTA DISTRIBUSI TNF-α GASTER TIKUS, DENGAN MEDIASI KORTISOL DAN IL–6 - Suparno Suparno (The East Java Biological Society, 2008)
Generally, distres which followed by psychiatric disorders still more medicinal practice controversial especially physically stressor roles on holistic health condition. Therefore, researches still more needed to explain and clarify the infl uences and the role of physically stressors on psychiatric disorders. This study used an psychoneuroimmunologic paradigm, which used posttest-only true experiment design for the research. About 24 female Rattus norvegicus strain Wistar had been used, they were devided into six groups. To investigate functional changes, we had been used hippocampus SERT distribution changes as mirror of central serotonergic malfunction changes. While, to investigate structural changes we had been inspected apoptosis index of hippocampus CA3 regions (hippocampus slicing). We also took the blood from the rats heart to examinate IL–6 and cortisol level, and gastric tissues for TNF-α level examination. Physical stressors lead to arise functional and structural changes include hippocampus SERT distribution, increases hippocampus apoptotic index, and increases TNF-α level, that fi nally arise the distress. These results of statistical analyses demonstrate that physical stressors tend to be mediated by serotonergic neurotransmission pathway. This study also support assumptions that psychological stressors caused and or related with gastrical changes.